Elites' and voters' attitudes towards austerity policies and their consequences in Greece and Portugal - Teperoglou, E. (2015)
This article analyses the attitudes of the political elite and voters in Greece and Portugal vis-à-vis the Troika bailouts, austerity policies and the attribution of responsibilities for the crisis. Using both elite and mass surveys with similar questions, the article explores to what extent the elites and voters share similar attitudes, what might explain possible differences between these two groups and between the two countries and what this information can tell us about the quality of political representation in Greece and Portugal. The differences between the countries are explained mainly by the severity of the crisis and austerity policies in each country, but also by the diversity of political conditions.